Norwegian use of the polar oceans as occupational arenas and exploration routes - Barr, Susan (Polar Record, 2001)
Publisher: Cambridge University Press
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; forskning; geografi; historie; oppdagelsesreiser; polarområdene

Norway's polar territories - Barr, Susan (Aschehoug, 1987)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Peter I. Øy; geografi; geologi; historie; polarområdene; polarpolitikk

Kulturminnevern i Antarktis: noe for ICOMOS? - Barr, Susan (Icomos nytt, 1989)
Keywords: Antarktis; Peter I. Øy; historie; kulturminneforvaltning

Den japanske antarktisekspedisjonen i 1912 - Barr, Susan (Polarboken, 2012)
Keywords: Antarktis; ekspedisjoner; historie

De første skiturene i Antarktis - Barr, Susan (Snø & ski: årbok, 2007)
Keywords: Antarktis; ekspedisjoner; historie; logistikk

Ekspedisjonsfotografi i polare områder - Barr, Susan (Bildet lever! : bidrag til norsk fotohistorie. 7, 1999)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; fotografi; historie; polarekspedisjoner; polarområdene

Polare jubileer i 1997 og 1998 - Barr, Susan (Polarboken, 1998)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie

Scott und Amundsen - Barr, Susan (Arktis Antarktis, 1997)
Keywords: Antarktis; ekspedisjoner; historie

Antarctica's cultural heritage: can ICOMOS help? - Barr, Susan (Icomos information, 1990)
Keywords: Antarktis; Sørishavet; historie; kulturminneforvaltning

Expedition photography in polar areas - Barr, Susan (Photoresearcher, 1997)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; fotografi; historie; polarekspedisjoner; polarområdene

Norske offentlige samlinger med kulturhistorisk polarmateriale - Barr, Susan (Norsk polarinstitutt, 1994)
Publication Title: Meddelelser
Keywords: Antarktis; polarforskning; polarhistorie; polarområdene; polarsamlinger

Roald Amundsens's Tent at the South Pole - Barr, Susan (Antarctic Resolution, 2021)
Keywords: Antarktis; Norge; Roald Amundsen; Sydpolsekspedisjonen; historie

International Polar and Geophysical Years - Barr, Susan (Antarctic Resolution, 2021)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Det internasjonale polaråret (IPY); forskning; internasjonal samarbeid

Norway and the Antarctic - Stephenson, Robert B; [Barr, Susan] (The Erebus and Terror Press, 2017)
Pages: 14 s. Publication Title: Norway and the Antarctic : SouthPole-sium v.3 Place: New Hampshire
Keywords: Antarktis; Nordmenn; norske ekspedisjoner; polarfarere

Polar settlements : location, techniques and conservation - Barr, Susan (red.); Chaplin, Paul (red.) (ICOMOS International Polar Heritage Committee, 2011)
Keywords: Antarktis; hvalfangststasjoner; kulturminnevern; polarforskning; polarområdene; turisme

Cultural heritage in the Arctic and Antarctic regions - Barr, Susan (red.); Chaplin, Paul (red.) (ICOMOS International Polar Heritage Committee, 2004)
Publication Title: Monuments and sites
Keywords: Antarktis; kulturminnevern; kulturvern; polarområdene

Historical Polar bases - preservation and management - Barr, Susan (red.); Chaplin, Paul (red.) (ICOMOS International Polar Heritage Committee, 2008)
Publication Title: Monuments and sites
Keywords: Antarktis; forskningsstasjoner; kulturminnevern; kulturvern; polarområdene

Whaler's cross on Deception Island - Barr, Susan; Downie, Rod; Sánchez, Rodolfo (Polar Record, 2004)
The cemetery at Whalers Bay, Deception Island, was the largest in the Antarctic prior to being partially buried and partially washed away during a volcanic eruption in 1969. In 2002 a wooden cross at Argentina's Decepción Station was identified as being that of the Norwegian whaler Peder Knapstad. It was removed, secured in a base, and re-erected at Whalers Bay.
Edition: 2004/01/19 Publisher: Cambridge University Press
Keywords: Antarktis; Deceptionøya; Sørishavet; kulturminneforvaltning; kulturminner

Roald Amundsen : tidenes polfarer - Barr, Susan; Amundsen, Roald; Ekeberg, Jan Ove (Stenersen forl., 2005)
Keywords: Antarktis; Belgica ekspedisjon; Roald Amundsen; Sydpolsekspedisjonen; biografier; dagbøker; oppdagelsesreiser

Ekspedisjoner og begivenheter - Barr, Susan (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; oppdagelsesreiser; polarfarere